Studi Komparasi Pembelajaran Pendekatan Tarl Gaya Belajar ,CRT dan Integrasi falam Peningkatan Keterampilan Bola Basket - Oktavia, Hasna Tri; Setianingsih, Mega Rayhan Yuni; Assidiqi, Muadz; Raharjo, Hermawan Pamot (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
The purpose of this research is to analyze the most effective learning approaches in physical education. The subjects of this study are 11th-grade students at SMK Negeri H. Moenadi Ungaran (SPMA) with a total of 4 experimental classes and 1 instrument testing class. The design of this research uses mixed methods with the type of mixed methods being concurrent embedded design with a tendency towards quantitative-qualitative research. Data will be analyzed using IBM SPSS Version 25. The results of this study indicate that all treatments had a significant impact on student learning outcomes. However, the highest sequential improvement comes from the Integration, Learning Style, TaRL, and CRT groups. Conclusion: Learning with the integration of CRT, TaRL, and learning styles has a positive impact compared to separate approaches. Keywords: Learning Approaches, TaRL, CRT, Learning Styles, PJOK